User Motivations in Protecting Information Security: Protection Motivation Theory Versus Self-Determination Theory. Issue 4 (2nd October 2017) - Menard, Philip; Bott, Gregory J.; Crossler, Robert E.
Abstract: Managers desiring to protect information systems must understand how to most effectively motivate users to engage in secure behaviors. Information security researchers have frequently studied individuals' performance of secure behaviors in response to threats. Protection motivation theory (PMT) has been used to explain individuals' propensity to engage in voluntary secure behaviors, but the adaptation of this theory has yielded inconsistent results. Motivation as a measurable construct, as derived from self-determination theory (SDT), has never been included in or compared against PMT. In this study, we construct security messages that appeal to individuals' intrinsic motivation, rather than fear, as a way to elicit secure responses. Using three sets of respondents, we integrated the SDT and PMT models and compared the native models in the context of security behaviors. We demonstrate that by using data- and individual-focused appeals and providing choices for users, managers may observe greater intention to engage in secure behavior among employees.